2019
DOI: 10.1007/978-981-13-6661-1_29
|View full text |Cite
|
Sign up to set email alerts
|

Provenance Analysis for Instagram Photos

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…While these tools enrich the user experience, they may also manipulate the images in a way that may make the SPN-based provenance analysis method ineffective. As a preliminary investigation in [25], we found some image filters of Instagram may cause significant performance drop of existing SPN-based SOC methods. In this work, we will further investigate the effects of Instagram filters and propose a new method to mitigate the impact of image filtering.…”
Section: Background and Related Workmentioning
confidence: 90%
See 2 more Smart Citations
“…While these tools enrich the user experience, they may also manipulate the images in a way that may make the SPN-based provenance analysis method ineffective. As a preliminary investigation in [25], we found some image filters of Instagram may cause significant performance drop of existing SPN-based SOC methods. In this work, we will further investigate the effects of Instagram filters and propose a new method to mitigate the impact of image filtering.…”
Section: Background and Related Workmentioning
confidence: 90%
“…We are particularly interested in the effects of image filters on Instagram as it is one of the most popular photo-sharing platforms. Our recent work in [25] has preliminarily shown that some Instagram image filters are particularly harmful to SPN-based clustering. In this work, we conduct further investigation on images from Instagram to gain a better understanding of how SPN-based clustering methods are affected by these filters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel method for PRNU fingerprint estimation is presented in [9] taking into account the effects of video compression on the PRNU noise through the selection of blocks of frames with at least one non-null DCT coefficient. In [10], a VGG network is employed as classifier to detect the images according to the Insta- gram filter applied, aiming at excluding certain images in the estimation of the PRNU and thus improving the reliability of the device identification method for Instagram photos. The VISION dataset [15] is employed by many methods reviewed in this Section.…”
Section: Device and Model Identification: Perfect Knowledge Methodsmentioning
confidence: 99%
“…The social media identification problem has been widely studied for image files with promising results [3,7,8], employing machine learning classifiers. Recently, Quan et al [9] showed that by using convolutional methods it is possible to recognize Instagram filters and attenuate the sensor pattern noise signal in images. Amerini et al [10] introduced a CNN for learning distinctive features among social networks from the histogram of the discrete cosine transform (DCT) coefficients and the noise residual of the images.…”
Section: Introductionmentioning
confidence: 99%